The Impact of Breast Symmetry on Eye Movement and Gaze Pattern: An Eye-Tracking Investigation. (17th July 2021) - Moellhoff, Nicholas; Kandelhardt, Chiara; Ehrl, Denis; Kohler, Lukas; Koban, Konstantin; Giunta, Riccardo E; Guertler, Anne; Mardini, Samir; Cotofana, Sebastian; Frank, Konstantin
Abstract: Background: The objective assessment of beauty remains challenging despite ongoing research efforts. A new method of objectively determining the aesthetic appeal of body features by analyzing gaze patterns and eye movements has recently been investigated. Objectives: The objective of this study was to assess, by means of objective eye-tracking technology, differences in the gaze patterns of observers presented with standardized 3-dimensional images showing different degrees of breast asymmetry. Methods: A total of 83 Caucasian study participants with a mean age of 38.60 (19.8) years were presented with 5 images depicting varying degrees of breast asymmetry. In addition to the assessment of eye movements, participants were asked to rate the aesthetic appeal and the asymmetry of the breasts on a 5-point Likert scale. Results: Overall, the data showed that participants' rating of the breasts' aesthetic appeal was inversely related to the level of asymmetry. The mean [standard deviation] time until fixation was shortest for the image depicting the greatest breast asymmetry (50 cc) at 0.77 [0.7] seconds ( P < 0.001). In addition, the mammary region was also viewed longest in this image at 3.76 [0.5] seconds ( P < 0.001). A volume difference of 35 cc between breasts deflected the observers' gaze significantly toward the larger of the asymmetric breasts ( P < 0.001). Conclusions: Surgeons should focus on achieving symmetric breast volume (ie, differences <35 cc between breasts) to avoid noticeable asymmetry with regard to breast size.